Neural Habituation to Painful Stimuli Is Modulated by Dopamine: Evidence from a Pharmacological fMRI Study - Bauch, Eva M.; Andreou, Christina; Rausch, Vanessa H.; Bunzeck, Nico (Frontiers in Human Neuroscience, 2017)
In constantly changing environments, it is crucial to adaptively respond to threatening events. In particular, painful stimuli are not only processed in terms of their absolute intensity, but also with respect to their context. While contextual pain processing can simply entail the repeated processing of information (i.e. habituation), it can, in a more complex form, be expressed through predictions of magnitude before the delivery of nociceptive information (i.e. adaptive coding). Here, we investigated the brain regions involved in the adaptation to nociceptive electrical stimulation as well as their link to dopaminergic neurotransmission (placebo/haloperidol). The main finding is that haloperidol changed the habituation to the absolute pain intensity over time. More precisely, in the placebo condition, activity in left postcentral gyrus and midcingulate cortex increased linearly with pain intensity only in the beginning of the experiment and subsequently habituated. In contrast, when the dopaminergic system was blocked by haloperidol, a linear increase with pain intensity was present throughout the entire experiment. Finally, there were no adaptive coding effects in any brain regions. Together, our findings provide novel insights into the nature of pain processing by suggesting that dopaminergic neurotransmission plays a specific role for the habituation to painful stimuli over time.